Advances in precision oncology using patient-derived organoids and functional biomaterials - Singh, Hina; Mijakovic, Ivan; Singh, Priyanka (Frontiers in Cell and Developmental Biology, 2025)
Despite major advances in oncology, cancer therapy continues to face persistent challenges due to intratumoral heterogeneity, drug resistance, and the poor clinical translation of experimental therapeutics. Conventional preclinical models such as 2D cultures and animal systems often fail to accurately recapitulate the tumor microenvironment immune contexture, and patient-specific variability limiting their predictive power. While nanomedicine and advanced drug delivery platforms offer promising solutions, their translational success is hindered by insufficient integration with physiologically relevant tumor models. In this review, we critically examine how patient-derived organoids derived from patient tumors serve as next-generation platforms for modeling cancer heterogeneity, therapeutic response, and biomarker discovery. We further explore how the integration of PDOs with functional biomaterials, extracellular matrix mimetics, and organ-on-chip systems enables dynamic co-culture environments that capture tumor–stroma–immune interactions with high fidelity. By linking the biological underpinnings of resistance, such as genetic mutations, altered signaling, metabolic rewiring, and immune evasion, with smart biomaterial design and drug screening workflows, we propose a unified roadmap for precision oncology. Additionally, we highlight the emergence of PDO biobanks, co-culture innovations, and high-throughput phenotypic screening as essential tools for improving clinical translation. This interdisciplinary synthesis underscores the transformative potential of PDO-based platforms in accelerating personalized cancer therapy.